الأفعال الكلامية التوجيهية في فيلم كارتوني فصحة فواز ونورة لسكردي حسن الدين (دراسة تداولية) - Annisaa Nurjayanti, Vina Bella; Rahtikawati, Yayan; Heryani, Yani; Wati, Wiwit Rahma; Zainul Mustofa, Ady Muh. (Departement of Arabic Language and Literature, 2026)
This study discusses the speech form and function of directive speech acts in the two classical Arabic cartoons, Fawaz and Naurah, produced by Sakardi Hasanudin's YouTube channel and iEN Youtube Channel. The classical Arabic cartoon, Fawaz and Naurah, depicts a family that offers many lessons about education in everyday life. The objectives of the study are: 1) To identify the form of directive speech acts in the dialogue of the Arabic cartoon, Fawaz and Naurah. 2) To identify the function of directive speech acts in the Arabic cartoon, Fawaz and Naurah. The method used in this research is the library method, using several scientific research sources in the form of books or magazines related to the title or topic to be discussed. This research is descriptive of the object to be studied. The research steps : 1) Writing down directive speech acts founded in Fawwaz and Nauroh cartoon; 2) Determining speech acts types; 3) Analysing speech acts from eight components purpose (SPEAKING); 4) Analysing the meaning purposed behind the data from speech acts types and its function. Results of the analysis of direct directive speech acts and indirect directive speech acts in the cartoon, Fawaz and Naurah: 3 data for directive speech acts and 3 data for indirect directive speech acts.